Os desafios dos dirigentes na integração das culturas e pessoas nos processos de fusão e aquisição - Sanson, Marco Antonio (2016)
The phenomenon of globalization has caused many changes in the world scene, bringing greater integration between companies of different nationalities, and the expansion of its business worldwide. In order to ensure the continued growth and competitiveness in their markets the companies have adopted various methods, being mergers and acquisitions one of its main, since this strategy is responsible for the market power, the scale economies gain and the access to technological innovations. From these findings the present study was designed with a national company, which held merger with another of the same sector. He sought to understand the role played by the leaders and the challenges faced in the integration process, focusing on organizational culture and people management. The research has a quantitative and qualitative nature by conducting case study. The sample was composed of two professional categories: partners and employees, who participated in the merger process and have remained in the company until the date of the survey. The study was composed of 6 semistructured interviews with company partners and 43 questionnaires with others employees. In this research were made statistical analysis using SPSS 17.0 software (Mann-Whitney and Kruskal Wallis) and the SPAD program 4.1 (lexical and semantic analysis). The main challenges and problems overcome by the leaders in the integration of the companies were caused by the formation of "cliques" among employees and the initial resistance of the teams to adopt a more complex and bureaucratic work methodology. It is noteworthy that the problems encountered during the process of post-merger company, were relate to the integration of people and cultures. This confirms the points presented in the theoretical framework in which these problems are still the most sensitive and require greater concern among leaders for ensure the success in a merger and acquisition process and achieve the proposed objectives. The study results show that when there is effective participation of leaders in the integration of culture and people, the problems caused by the process are overcome more quickly, which reduced the stress of this operation and generated more credibility in the work of leaders. This credibility in leadership was the keyfactor to the success of the post-merger